Unveiling New Horizons: AI-Driven Decision Support Systems in HRM - A Novel Bibliometric Perspective - Shantilawati, Irma; Suri, Oryza Intan; Sunarjo, Richard Andre; Anjani, Sheila Aulia; Robert, Dariari (Pandawan, 2025)
The integration of Artificial Intelligence (AI)-driven Decision Support Systems (DSS) in Human Resources Management (HRM) has become crucial for optimizing workforce management and enhancing decision-making processes. This bibliometric analysis investigates the research landscape of AI-driven DSS in HRM from 2015 to 2024, using data from the Dimensions database and analyzed through VOSviewer. Key trends, influential authors, and significant publications are identified, revealing the dominant roles of the United States, China, and India, with institutions like MIT, Stanford University, and IIT Delhi leading in productivity and impact. Notable contributors such as Dwivedi, Lowry, and Bose are highlighted for their practical and theoretical advancements in the field. Influential journals including